Evaluation of the potential for greenhouse gas (CO2 , CH4 ) emissions in the southern São Paulo coastal region, Cananéia-Iguape system - Elaine C. Araujo; Thais Correa; Izabel da S. Andrade; Fernanda de M. Macedo; Marcia T. Marques; Thais Andrade; Carlos Eduardo Souto-Oliveira; Elisabete S. Braga; Maria de F. Andrade; Eduardo Landulfo (Ocean and Coastal Research)
The emissions of CH4 and CO2 , the primary greenhouse gases, have a significant impact on radiative forcing. This study investigated these gases along the Cananéia-Iguape estuarine system on the southern coast of the State of São Paulo, Brazil, which is a mangrove region characterized by low anthropogenic impact and a sparse population. As such, this area provides an ideal location for identifying natural emissions and background concentrations. The data for this study were collected using a portable gas analyzer (LGRICOSTM GLA131), known for its high sensitivity and precision in detecting gases, mounted on a research boat. The results obtained were promising for both gases. A small variability in CH4 concentrations was observed along the route, ranging from 1.84 ppm to 1.95 ppm, while CO2 , showed greater variation in values obtained during routes, ranging from approximately 411 ppm to 575 ppm. This study underscores the importance of investigating areas with minimal environmental impact. Together with future analyses, this research should help improve Greenhouse Gas (GHG) inventories in Brazil by providing valuable baseline data for comparisons with more impacted areas.